Mass- and Energy-Conserved Numerical Schemes for Nonlinear Schrödinger Equations (Communications in Computational Physics, 2019)
n this paper, we propose a family of time-stepping schemes for approximating general nonlinear Schrödinger equations. The proposed schemes all satisfy bothmass and energy conservation (in a modified form for the latter). Truncation and dispersion error analyses are provided for four proposed schemes. Efficient fixed-pointiterative solvers are also constructed to solve the resulting nonlinear discrete problems.As a byproduct, an efficient one-step implementation of the BDF schemes is obtainedas well. Extensive numerical experiments are presented to demonstrate the convergence and the capability of capturing the blow-up time of the proposed schemes.